Wolbachia occurrence in planthopper (Hemiptera: Delphacidae) vectors of cereal viruses in Argentina - Mattio, Maria Fernanda (2015)
Maize (Zea mays L.) and wheat (Triticum aestivum L.) are the most important cereal crops for the Argentinean economy and are affected by several diseases. Different planthopper species transmit causal agents of some of those diseases, including Mal de Río Cuarto virus, barley yellow striate mosaic virus, and the recently proposed maize yellow striate virus. Many planthopper species are sap feeders and therefore are expected to host bacteria providing essential nutrients lacking in the diet. Previous studies have evidenced that some of these bacterial symbionts are involved in the virus transmission. Wolbachia is a group of obligate intracellular bacteria infecting numerous arthropod species and causing reproductive alterations in their hosts. These bacteria have been detected in planthopper species, considered rice pests in various regions of the world. To date, Wolbachia infection status of planthopper species of Argentina is unknown. Amplification by PCR and sequencing of 16S rDNA, wsp- and ftsZ-specific genes demonstrated Wolbachia infection in Caenodelphax teapae (Fowler), Delphacodes kuscheli Fennah, Pyrophagus tigrinus Remes Lenicov & Varela, Tagosodes orizicolus (Muir), and Toya propinqua (Fieber). This is the first report of Wolbachia in delphacid vectors of viruses affecting maize and wheat. An understanding of the bacterial diversity harbored by these insect vectors could lead to new options for future management of diseases of economically important crops in a developing country.